A balanced-force control volume finite element method for interfacial flows with surface tension using adaptive anisotropic unstructured meshes. (15th October 2016) - Xie, Zhihua; Pavlidis, Dimitrios; Salinas, Pablo; Percival, James R.; Pain, Christopher C.; Matar, Omar K.
Highlights: A new CV-FE method is presented for 3D interfacial flows with surface tension. A new balanced-force algorithm for the CSF model on unstructured meshes is proposed. Two approaches are proposed for accurate curvature calculation on unstructured mesh. The numerical framework also features an anisotropic adaptive mesh algorithm. The method is validated with several benchmark problems for interfacial flows. Abstract: A balanced-force control volume finite element method is presented for three-dimensional interfacial flows with surface tension on adaptive anisotropic unstructured meshes. A new balanced-force algorithm for the continuum surface tension model on unstructured meshes is proposed within an interface capturing framework based on the volume of fluid method, which ensures that the surface tension force and the resulting pressure gradient are exactly balanced. Two approaches are developed for accurate curvature approximation based on the volume fraction on unstructured meshes. The numerical framework also features an anisotropic adaptive mesh algorithm, which can modify unstructured meshes to better represent the underlying physics of interfacial problems and reduce computational effort without sacrificing accuracy. The numerical framework is validated with several benchmark problems for interface advection, surface tension test for equilibrium droplet, and dynamic fluid flow problems (fluid films, bubbles and droplets) in two and three dimensions.